A history of the homosexual liberation front and left-wing politics in Argentina - Insausti, Santiago Joaquin (2019)
Emerging during the seventies in Argentina during the political radicalization and inspired by the rise of the New Left, the Homosexual Liberation Front (Spanish acronym FLH) attempted an alliance with a variety of organizations on the left. My research will trace the mutations in the political discourse and strategies shaping the attempts at allying with the left-wing over time, as well as the tensions and contradictions that it created among both the rank and file, within the FLH, and other organizations.